How to Guarantee the Save Term of Operation for the Mechanical Parts of Friction - Kirill Voinov (Current Approaches in Science and Technology Research Vol. 7, 2021)
Introduction: Huge amount of the mechanical systems (mechanisms, devices, test benches, machines, vehicles and so on) have very many mobile pairs of friction in their design. During the operation these parts begin to deteriorate with the different rate. The main factor to appear the limit term of normal operation is the permissible wear for each pair of friction. It is not good if each part will stop its normal operation in a different time/period of operation. Consequently, there is very important problem connected with the cycle of manufacture to get the situation when practically all pairs of friction will their technical resource the same/identical. Obviously, the analogous situation takes place to the parts if we make the analysis about their resistance to shock, to bending strength and so forth. If the rate of the appearance of the destructions is quite different for many parts, therefore there is no possibility to put/appoint the united term of the limit operation for the mechanical system to have the highest reliability. In this article there are one method and recommendations with examples how to overcome this negative situation in practice.